Global forces on the COMPASS-U wall during plasma disruptions. (4th August 2021) - Yanovskiy, V.V.; Isernia, N.; Pustovitov, V.D.; Scalera, V.; Villone, F.; Hromadka, J.; Imrisek, M.; Havlicek, J.; Hron, M.; Panek, R.
Abstract: First, it is shown that during electromagnetic transients in COMPASS-U the poloidal field coils must drain sizeably the current from the vessel and, therefore, reduce disruption forces and their duration. Next, the role of poloidal eddy current (which is absent in some approaches) in the dynamics of vertical and radial forces is found to be essential. Finally, to verify the CarMa0NL modelling for COMPASS-U, the numerical results are cross-validated with general analytical predictions (Pustovitov 2015 Nucl. Fusion 55 113032): the computed vertical force on the tokamak wall is found to be almost zero during rapid (jump-like) transients, as it should be because of strong skin-effect. This test proves the credibility of the simulation model and computational realization.